Marine prey processed with stone tools by burmese long-tailed macaques (Macaca fascicularis aurea) in intertidal habitats - Gumert, Michael David (2013)
Long-tailed macaques (Macaca fascicularis) feed opportunistically in many habitats. The Burmese subspecies (M. f. aurea) inhabits coastal areas in southwestern Thailand and Myanmar, and some of their populations have adapted lithic customs for processing encased foods in intertidal habitats. We investigated the diet of such macaques in Laemson National Park, Thailand, and identified the variety of foods they processed with stones. We conducted 36 shore surveys to study tool sites following feeding activity, during which we counted the minimum number of individual (MNI) food items found at each site. We identified 47 food species (43 animals and four plants), from 37 genera. We counted 1,991 food items during surveys. Nearly all were mollusks (n = 1,924), with the small remainder primarily consisting of crustaceans and nuts. The two most common foods, rock oysters (Saccostrea cucullata; n = 1,062) and nerite snails (Nerita spp.; n = 538), composed 80.2% of our sample. Four prey species comprised 83.2% of the sample (MNI = 1,656), S. cucullata (n = 1,062), Nerita chamaeleon (n = 419), Thais bitubercularis (n = 95), and Monodonta labio (n = 80). Macaques selected a wide variety of foods. However, they heavily concentrated on those that were abundant, easy to access, and sufficiently sized. The Burmese long-tailed macaque stone-processed diet, which focuses on intertidal marine prey, differs from Sapajus and Pan, who use stones primarily for encased nuts and fruits. In terms of diversity of foods exploited, coastal stone-based predation by macaques resembles the diet of coastal-foraging humans (Homo sapiens sapiens). Am J Phys Anthropol, 2012.